Lifestyle, Social Media Marketing dan Price Discounts sebagai Faktor Strategis dalam Keputusan Pembelian Prior.id di Sidoarjo - Nonik Atika Aprilia Rosa; Dewi Komala Sari; Misti Hariasih (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to examine the influence of lifestyle, social media marketing, and price discounts on the purchase decision of Prior.id products in Sidoarjo. The approach used was descriptive quantitative with a population of 96 Prior.id consumers in the Sidoarjo area who were selected by purposive sampling. Data was collected through a questionnaire using the Likert scale and analyzed with the help of the SmartPLS 4 program to test the validity, reliability, and direct influence between variables. The results of the study show that these three variables have a positive and significant effect on purchasing decisions. Specifically, lifestyle motivates consumers to choose products that suit their identity and lifestyle, social media marketing increases trust and interaction that supports purchasing decisions, while price discounts act as financial incentives that speed up the decision-making process. This research confirms the importance of a marketing strategy that integrates aspects of lifestyle, social media, and price discounts in an effort to increase sales volume and customer loyalty Prior.id in Sidoarjo.